Efektivitas Program Pemberdayaan UMKM Berbasis Digital terhadap Pendapatan Pelaku Usaha: Studi di Kabupaten Banyumas - Ramadhan, Ahmad Fadli; Arya Saputra, Dimas (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to examine the effectiveness of digital-based MSME empowerment programs on business income in Banyumas Regency. The research adopts a quantitative approach with an explanatory design. Data were collected through a survey of MSME actors who participated in digital empowerment programs, including digital literacy training, social media utilization, e-commerce adoption, and digital payment systems. Data analysis employed descriptive statistics and simple linear regression. The findings indicate that digital-based MSME empowerment programs have a positive and significant effect on business income. Income growth is driven by expanded market access, improved transaction efficiency, and more effective digital marketing strategies. However, the impact of the program varies among MSME actors, depending on digital literacy levels, business sectors, and the intensity of technology utilization. This study concludes that digital empowerment programs are an effective strategy for increasing MSME income and strengthening local economic development. The results provide practical implications for local governments and stakeholders to design sustainable and needs-based digital empowerment policies for MSMEs.